Clinical case of Carpenter syndrome (autoimmune-polygundularsyndrome 2) in the practice of an endocrinologist (Bangladesh Journal of Medical Science, 2019)
Presentation of case: patient 36 years old, appealed to complaints about changing the color of the skin, reducing body weight by 10 kg in 2 months, expressed general weakness, lowering blood pressure, reducing sexual desire.Discussion: prescribed treatment: insulin therapy (aspart, degludec) day dose 42 OD, levothyroxine 100 mcgr/day, vitamin E, selenium 100 mcgr, chorionic gonadotrophin 1500 OD intramuscularly once per week, monthly courses with the same break. After the therapy, the patient’s condition improved. Repeatedly the patient appeared on the review 6 months after treatment. Hyperpigmentation of the skin and natural areas of pigmentation are reduced, there is a stabilization of blood pressure at a level of 120 / 70-110 / 70 mm Hg, reduction of clinical symptoms, achieved target level of glycemia and hormonal blood parameters the target glycemia level was reached (4.6-5.1 mmol / L), glycosylated hemoglobin (8.1%) and hormonal blood parameters (TTG 3.4 mmol / L) cortisol serum 1.7 μg / dl (norm 6.2-19.4 μg / dl), testosterone free 3.4 pg / ml (N 1.7-8.2), total testosterone - 12.28 (N 8.64 - 29 nmol / l), sex steroid binding globulin (CHD) (67 nmol / l, at the rate of 13-71 nmol / l, ), testosterone free 8.9 pg / ml (N 8.8 - 42.5 pg / ml).Conclusions: Decomposition of adrenal insufficiency (decrease in glucocorticoids as contrinsular hormone) can lead to untypical cours of diabetes with steaolyhipoglicemia in autumne-summer period and normalizabionglycemia glycemia in winter-autumne period. Presents of 2-3 decompensate, endocrine diseases in the same moment suppresses pronounced typical symptomatics each of them precedes with erased or disguised picture.Bangladesh Journal of Medical Science Vol.18(3) 2019 p.646-650